DIVERSI SEBAGAI UPAYA MEMINIMALISIR PENYELESAIAN PERKARA ANAK YANG BERKONFLIK DENGAN HUKUM - Kolono, Sucipto; Nurmayana, Suri; Juliani, Wenny; B, Meky Yadi Saputra; Widjajanti, Ermania (Ensiklopedia of Journal, 2025)
Abstract: This paper discusses the implementation of diversion as a form of solution to criminal cases of children with legal problems outside the formal legal institution mechanism. Diversion is seen as a humanist solution because it puts forward the basis of restorative justice and protection of children's rights, as contained in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA). This study uses a theoretical approach through child protection theory and restorative justice theory, and highlights the effectiveness of diversion in practice, including various challenges faced from normative, structural, cultural, to technical operational aspects. The results of the study show that the implementation of diversion has not run optimally due to limited regulations, lack of understanding of the apparatus, lack of supporting infrastructure, and community resistance to non-retributive approaches. In addition, the inconsistency of evaluative data and uneven implementation between regions also worsen the condition. Therefore, it is necessary to strengthen regulations, increase the capacity of human resources, enlighten the community, and synergize between institutions to ensure the implementation of effective and equitable diversion. Diversion that is carried out substantially is expected to be a means of social rehabilitation and long-term protection for children in the Indonesian legal system.Keywords: diversion, children in conflict with the law, restorative justice, child protection, UU SPPA.